Design and Construction of a Web-Based Digital Community Administration Service Information System in Rimbo Ilir District: Rancang Bangun Sistem Informasi Pelayanan Administrasi Digital Masyarakat Berbasis Web Pada Kecamatan Rimbo Ilir - Rahmalia Ertika Putri; Evi Yulia Susanti; Fauzi Tri Yuniko (Journal of Vocational Education and Information Technology (JVEIT), 2026)
Administrative services in Rimbo Ilir District are still managed manually, resulting in inefficient document submission, data recording, and document management processes. This study aims to design and develop a web-based Digital Community Administrative Service Information System to support administrative services in Rimbo Ilir District. The system was developed using the Waterfall software development model. Data were collected through observation, interviews, literature review, and documentation. The system was designed using the Unified Modeling Language (UML) and implemented using the Python programming language with a MySQL database. Functional testing was conducted using the Black Box Testing method. The results show that the developed system provides online document submission, document upload, application verification by administrators, application status tracking, and administrative report generation. Based on the testing results, all major system functions operated as intended, indicating that the system can support more effective, efficient, and integrated administrative services in Rimbo Ilir District.